Inovasi Pengembangan Sistem Pembelajaran Digital Untuk Meningkatkan Literasi Digital Siswa Sekolah Dasar - Kadek Ayu Kartika Dewi; Kadek Dinda Dwi Suryani; Ayu Komang Lestari Dewi; I Wayan Halmahera D. Wijaya; Luh Putu Eka Bellantari; Ni Kadek Asri Damayanti (Indonesian Journal Publisher, 2026)
Digital transformation in education has encouraged changes in learning systems, particularly in developing students’ competencies required in the 21st century. One essential skill that needs to be developed from elementary school is digital literacy, which refers to the ability to access, understand, evaluate, create, and use digital information effectively and responsibly. This study aims to analyze innovations in digital learning system development and their implications for improving elementary school students’ digital literacy. This research employed a literature review method with a qualitative approach through the identification, selection, analysis, and synthesis of relevant national and international journal articles, conference proceedings, academic books, and educational policy documents published from 2015 to 2025. Data were collected through searches in several academic databases and analyzed using content analysis techniques to identify patterns, strategies, and the effectiveness of digital learning technology implementation. The findings reveal that innovations in digital learning systems contribute positively to improving students’ digital literacy through several technological approaches, including Learning Management Systems (LMS) and digital learning platforms, Android-based mobile learning, Artificial Intelligence (AI) and Augmented Reality (AR), as well as interactive multimedia and video-based learning. These technologies enhance students’ abilities to access information, evaluate digital sources, communicate, collaborate, develop creativity, and improve critical thinking skills. However, the implementation of digital learning systems is still influenced by factors such as technological infrastructure, teacher readiness, digital access, and learning environment support. This study concludes that interactive, adaptive, and student-centered digital learning systems are effective strategies for enhancing elementary school students’ digital literacy and supporting sustainable educational transformation.